Development of Motion and Force Learning E-Modules Based on PjBL-STEM-Jigsaw to Improve Student Creativity - Ayu Ariyani; Irvan Permana; Anna Permanasari (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2024)
This research aims to develop a PjBL-STEM-based learning e-module to improve student creativity in motion and force material. The development of this research is important as a parameter of 21st century skills that require students to have critical thinking, creative, collaborative and communication to face the era of Education 4.0. This research method uses Research and Development (R&D). The selected R&D design is ADDIE design which consists of 5 stages (Analiysis, Design, Development, Implementation, Evaluation). Class VII students (N=36) were involved as research subjects taken by purposive sampling technique. Data were collected through creativity test, student response questionnaire and observation sheet. The data processing technique used paired sample t-test and then N-Gain test. The results of the analysis showed that after using the PjBL-STEM-based learning e-module there was an increase in creativity with an N-Gain value of 60% in the medium category. Testing the effectiveness of learning e-modules using SPSS paired sample t-test showed a result of 0.001 which means that PjBL-STEM-based learning e-modules have an effect on student creativity. The descriptive average of creativity increased by 29.83%. In addition, students gave a positive response to the learning e-module which made it easier to understand the material.